Fostering a Developmental Educational and Creative Environment for Children with Special Educational Needs in the Bulgarian Inclusive Education - Julia G. Doncheva (ARPHA Proceedings, 2020)
Theoretical and methodological grounds for topic research: An important skill for a successful and fulfilling life is the ability for adaptive and positive behavior, which enables people to deal effectively with the demands and challenges of everyday life as defined by World Health Organization. In particular, life skills are a group of psychosocial competencies and interpersonal skills that help people make informed decisions, solve problems, think critically and creatively, communicate effectively, build healthy and sustainable relationships, show empathy to others, lead a healthy and effective way of life, etc. Life skills contribute to personal actions and relationships with others, as well as to actions that aim to change the environment in a way that is beneficial to people’s health.Research area: This publication analyses options to alleviate the state of distress present both in children with special needs as well as in their parents since it is the parents, who, together with educators, work in synergy for a common cause – the effective development and improvement of a child's autonomy. The practical dimension is related to the search for a coherent link in the application of creativity as a formative and personality-developing process with a sustainable trend towards adaptation, socialization, and a fulfilling way of life for the persons/children with special educational needs.Objectives, methods, results, conclusions, and recommendations: For the topic, a small-scale study with parents of children with disabilities was carried out to find out the main problems related to their children’s socialization and learning process, to highlight them and work towards their solution. From a more global perspective, the question of procedural modeling is also addressed to influence positively the overall health of children with special educational needs, their full integration, as far as it is possible, which should contribute to their happiness and ultimately, the prosperity of the community. Process modeling as an activity usually implies the need to change the process or to identify problems to be corrected. This transformation can be realized in different ways including the use of information and communication technologies and resources (ICTS) as necessary to modify the process. Change management programs, techniques or models are desirable, as they will contribute to the successful application of the processes in practice.